2023
DOI: 10.3762/bjoc.19.145
|View full text |Cite
|
Sign up to set email alerts
|

Aldiminium and 1,2,3-triazolium dithiocarboxylate zwitterions derived from cyclic (alkyl)(amino) and mesoionic carbenes

Nedra Touj,
François Mazars,
Guillermo Zaragoza
et al.

Abstract: The synthesis of zwitterionic dithiocarboxylate adducts was achieved by deprotonating various aldiminium or 1,2,3-triazolium salts with a strong base, followed by the nucleophilic addition of the in situ-generated cyclic (alkyl)(amino) or mesoionic carbenes (CAACs or MICs) onto carbon disulfide. Nine novel compounds were isolated and fully characterized by 1H and 13C NMR, FTIR, and HRMS techniques. Moreover, the molecular structures of two CAAC·CS2 and two MIC·CS2 betaines were determined by X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…1 Reacting CS 2 with a free carbene, either preformed or generated in situ by deprotonating an azolium salt with a strong base, is indeed the most common strategy to obtain these betaines (Scheme 1B). 2,3 Yet, back in 1965, Winberg and Coffman isolated the first representatives of these inner salts upon cleavage of enetetramines with CS 2 in xylenes (Scheme 1A). 4 More recently, we showed that (benz)imidazol(in)ium-2-dithiocarboxylates could also be readily obtained from their azolium salt precursors and CS 2 using cesium carbonate as a weak inorganic base under mild aerobic conditions, thereby avoiding the intermediacy of air-and moisture-sensitive NHCs (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%
“…1 Reacting CS 2 with a free carbene, either preformed or generated in situ by deprotonating an azolium salt with a strong base, is indeed the most common strategy to obtain these betaines (Scheme 1B). 2,3 Yet, back in 1965, Winberg and Coffman isolated the first representatives of these inner salts upon cleavage of enetetramines with CS 2 in xylenes (Scheme 1A). 4 More recently, we showed that (benz)imidazol(in)ium-2-dithiocarboxylates could also be readily obtained from their azolium salt precursors and CS 2 using cesium carbonate as a weak inorganic base under mild aerobic conditions, thereby avoiding the intermediacy of air-and moisture-sensitive NHCs (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%